RBP4 increases lipolysis in human adipocytes and is associated with increased lipolysis and hepatic insulin resistance in obese women. Issue 5 (13th March 2020) - Kilicarslan, Murat; de Weijer, Barbara A.; Simonyté Sjödin, Kotryna; Aryal, Pratik; ter Horst, Kasper W.; Cakir, Hamit; Romijn, Johannes A.; Ackermans, Mariëtte T.; Janssen, Ignace M.; Berends, Frits J.; van de Laar, Arnold W.; Houdijk, Alexander P.; et al.
Abstract: Retinol‐binding protein‐4 (RBP4) is elevated in serum and adipose tissue (AT) in obesity‐induced insulin resistance and correlates inversely with insulin‐stimulated glucose disposal. But its role in insulin‐mediated suppression of lipolysis, free fatty acids (FFA), and endogenous glucose production (EGP) in humans is unknown. RBP4 mRNA or protein levels were higher in liver, subcutaneous adipose tissue (SAT), and visceral adipose tissue (VAT) in morbidly obese subjects undergoing Roux‐en‐Y gastric bypass surgery compared to lean controls undergoing elective laparoscopic cholecystectomy. RBP4 mRNA expression in SAT correlated with the expression of several macrophage and other inflammation markers. Serum RBP4 levels correlated inversely with glucose disposal and insulin‐mediated suppression of lipolysis, FFA, and EGP. Mechanistically, RBP4 treatment of human adipocytes in vitro directly stimulated basal lipolysis. Treatment of adipocytes with conditioned media from RBP4‐activated macrophages markedly increased basal lipolysis and impaired insulin‐mediated lipolysis suppression. RBP4 treatment of macrophages increased TNFα production. These data suggest that elevated serum or adipose tissue RBP4 levels in morbidly obese subjects may cause hepatic and systemic insulin resistance by stimulating basal lipolysis and by activating macrophages in adipose tissue, resulting in release of pro‐inflammatory cytokines that impair lipolysis suppression. While we have demonstrated this mechanism in human adipocytes in vitro, and correlations from our flux studies in humans strongly support this, further studies are needed to determine whether this mechanism explains RBP4‐induced insulin resistance in humans.